MODEL PEMECAHAN MASALAH BERDASARKAN HASIL PEMETAAN KOMPETENSI SISWA MATA PELAJARAN GEOGRAFI DI SMA PASAMAN BARAT - Rahmanelli Rahmanelli (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2013)
Abstract This study aims to map the problem of the SK/KD students who have not dominated the UN competency test subjects Geography 2008, 2009, and 2010. Research conducted at SMAN 1 Pasaman, SMAN 1 Kinali, and Private School Al Istiqamah West Pasaman. This research is a descriptive study that describes the: 1) identify the outcome document of UN 2008, 2009, and 2010, 2) mapping the SK/KD students who have not dominated the UN competency test < 60, 3) identify the causes of low absorption of students through observation and distributing questionnaires to the geography teacher, and the students of class XI, 4) formulate an alternative model of problem solving through group discussion forum (FGD) with supervisor, principals, teachers, supervisors, student representatives, parent representatives. Research found that: 1) mapping the results of competency tests that have not dominated the UN SK/Specific KD of 42.5 percent in 2008, the year 2009 was 32.5 percent, and in 2010 ranged from 40.0 percent, 2) the factors causing the low level of student mastery of the competency test by the UN due to school factors, and subjects factor, 3) Alternative models of problem solving through the development of instructional workshops, and designing alternative models of learning through field trips as a geography laboratory applications.